(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The excessive use of electronic media by adolescents, has been a rising concern in recent years over the impact of electronic media on the mental and physical health of adolescents. This study investigates the relationship between the amount of media that adolescents consume and the emotional and physiological well-being of these adolescents. A total of 1,590 students from 44 upper secondary schools in the Thrissur region of Kerala participated in the survey that we conducted using a technique known as simple random sampling. The examination of the data was carried out with the use of statistical techniques such as the t-test, Pearson correlation, and regression analysis. It was shown that those who engaged in excessive usage of electronic media were much more likely to have instances of stress, emotional challenges, and behavioural concerns. In addition, there was a definite negative association between the amount of time students spent engaging with electronic media and the levels of pleasure they reported having with their educational experience. Given the findings, it is imperative that the amount of time that adolescents spend consuming electronic media be restricted in order to protect both their mental and physical well-being. In this digital era, it is essential to have a comprehensive understanding of how the media influences young people. This study provides support for the development of strategies that aim to foster healthier habits of media use.